a+b=4,ab=-2,求代数式(4a-3b-2ab)-(a-6b+ab)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 21:08:58
a+b=4,ab=-2,求代数式(4a-3b-2ab)-(a-6b+ab)a+b=4,ab=-2,求代数式(4a-3b-2ab)-(a-6b+ab)a+b=4,ab=-2,求代数式(4a-3b-2ab
a+b=4,ab=-2,求代数式(4a-3b-2ab)-(a-6b+ab)
a+b=4,ab=-2,求代数式(4a-3b-2ab)-(a-6b+ab)
a+b=4,ab=-2,求代数式(4a-3b-2ab)-(a-6b+ab)
这个问题比较简单.
把原式去括号:
(4a-3b-2ab)-(a-6b+ab)
=3a+3b-ab
=3(a+b)-3ab
=3*4-[3*(-2)]
=12+6
=18
(4a-3b-2ab)-(a-6b+ab)=(3a+3b)-ab=3*4-2(-2)=18
(4a-3b-2ab)-(a-6b+ab)=3a+3b-3ab=3(a+b)-3ab=18
(4a-3b-2ab)-(a-6b+ab)
=3a+3b-3ab=3(a+b-ab)=3(4+2)=18
(4a-3b-2ab)-(a-6b+ab)
=4a-3b-2ab-a+6b-ab
=3a+3b-3ab
=3(a+b)-3ab
=3*4-3*-2
=12+6
=18
a+b=4,ab=-2,求代数式(4a-3b-2ab)-(a-6b+ab)
已知a-b=-1,ab=-2,求代数式(3a-4b-ab)-(a-2b+3ab)
已知ab/a+b=2,求代数式3a-4ab+3b/-a+3ab-b的值
已知9a^-4b^=0,求代数式a/b-b/a-(a^+b^/ab)
a+b=-2,ab=3,求代数式(4ab-10b)-[7a-(3ab-3a)]值?
已知a-b=5,ab=-4,求代数式5a^2b(a-b)-3ab(b-a)^2+5ab^2(b-a)的值
已知a-b=5,ab=-4,求代数式5a^2b(a-b)-3ab(b-a)^2+5ab^2(b-a)的值
已知a-b=5,ab=-4,求代数式5a^2b(a-b)-3ab(b-a)^2+5ab^2(b-a)的值
已知9a^2-4b^2=0,求代数式a/b-b/a-(a^2+b^2/ab)
已知9a^2-4b^2=0,求代数式a/b-b/a-(a^2+b^2/ab)
已知a=4,b=-3,求代数式ab-2a^2b+23
已知a-b=3,ab=-2,求代数式(2a+3b-2ab)-(a+4b+ab)-(3ab+2b-2a)的值
已知a-b=2,ab=-3,求代数式(2a+3b-2ab)-(a+4b+ab)-(3ab+2b-2a)的值?
已知a-b=3,ab=1,求代数式(2a+3b-2ab)-(a+4b+ab)-(3ab+2b-2a)的值?
已知a-b=3,ab=-3,求代数式(2a+3b-2ab)-(a+4b+ab)-(3ab+2b-2a)的值
已知a-b=3,ab=-3,求代数式(-a-4b-ab)-(2ab-2a-3b)-(3ab+2b-2a)
已知a-b=5,ab=-1,求代数式(22a+3b-2ab)-(a+4b+ab)-(3ab+2b-2a)的值.
已知1/a-1/b=2求代数式-3a+4ab+3b/2a-3ab-2b的值求代数式2a-3ab-2b分之3a+4ab+3b的值